2016
DOI: 10.1159/000452945
|View full text |Cite
|
Sign up to set email alerts
|

Transdifferentiation of Small Cell Carcinoma of the Urinary Bladder from Urothelial Carcinoma after Transurethral Resection of a Bladder Tumor, Intravesical Bacillus Calmette-Guerin Instillation, and Chemotherapy: A Case Report

Abstract: A 73-year-old male underwent transurethral resection of a bladder tumor in August 2010 and April 2011. Pathological examination revealed urothelial carcinoma. After the surgery, chemotherapy and intravesical Bacillus Calmette-Guerin instillation were performed. In September 2014, he once again underwent transurethral resection of the bladder tumor for recurrence, and was again diagnosed with urothelial carcinoma, pT2, by pathological examination. After neoadjuvant chemotherapy, radical cystectomy for tumor rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…This indicates that cells from 1 cancer phenotype can give rise to another phenotype, presumably through processes involving transdifferentiation. This is concordant with prior reports of therapy-induced transdifferentiation (52). Our model thus provides a resource for the investigation of this clinically impactful plasticity.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that cells from 1 cancer phenotype can give rise to another phenotype, presumably through processes involving transdifferentiation. This is concordant with prior reports of therapy-induced transdifferentiation (52). Our model thus provides a resource for the investigation of this clinically impactful plasticity.…”
Section: Discussionsupporting
confidence: 91%
“…It is more common in male than female patients, with a ratio of 3.3:1.0 10 . Most reported cases are mixed variants containing elements, such as UC, squamous cell carcinoma, and adenocarcinoma, as shown in our patient 5 . Both a recurrent bladder tumor containing SmCC and a primary SmCC of the urethra is extremely rare in female patients.…”
Section: Discussionmentioning
confidence: 50%
“…1 Moreover, recurrent bladder tumors with neuroendocrine differentiation are extremely rare with only five cases reported since 2000. [2][3][4][5][6] Herein, we describe the first case of simultaneous occurrence of both rare conditions; a recurrent urethral tumor showing neuroendocrine differentiation in a female patient after RC for conventional UC.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). As a result, a total of 15 cases with detailed cystoscopic and pathologic descriptions from 14 studies were identified [ [8] , [9] , [10] , 16 , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. The clinical characteristics of the selected cases were summarized in Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%